2004
DOI: 10.1124/jpet.103.059030
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism-Based Pharmacokinetic-Pharmacodynamic Modeling of 5-HT1AReceptor Agonists: Estimation of in Vivo Affinity and Intrinsic Efficacy on Body Temperature in Rats

Abstract: The pharmacokinetic-pharmacodynamic (PK-PD) correlations of seven prototypical 5-HT 1A agonists were analyzed on the basis of a recently proposed semi-mechanistic PK-PD model for the effect on body temperature. The resulting concentration-effect relationships were subsequently analyzed on the basis of the operational model of agonism to estimate the operational affinity (pK A ) and efficacy (log ) at the 5-HT 1A receptor in vivo. The values obtained in this manner were compared with estimates of the affinity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…However, flesinoxan_s EC 50 required adjustment in order to adequately predict the hypothermic and cortisol response in man. In this respect it is important to note that in a meta-analysis of various 5-HT 1A receptor agonist effects on hypothermia Zuideveld et al (17) have shown that the affinity of flesinoxan is underestimated by approximately a factor 30. This apparent inconsistency can be explained by either a large difference in receptor reserve or a disproportionate difference in flesinoxan blood and effect site concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, flesinoxan_s EC 50 required adjustment in order to adequately predict the hypothermic and cortisol response in man. In this respect it is important to note that in a meta-analysis of various 5-HT 1A receptor agonist effects on hypothermia Zuideveld et al (17) have shown that the affinity of flesinoxan is underestimated by approximately a factor 30. This apparent inconsistency can be explained by either a large difference in receptor reserve or a disproportionate difference in flesinoxan blood and effect site concentration.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of various 5-HT 1A receptor agonist effects on hypothermia, Zuideveld et al (17) have shown that the affinity of flesinoxan is underestimated by approximately a factor 30. The underestimation is likely to be due to the fact that flesinoxan is subject to an active transport mechanism, resulting in a drug receptor association rate constant (Ka), estimate based on blood concentrations which may not be representative of the concentration at the site of the 5-HT 1A receptor (18).…”
Section: Allometric Scaling Of the Pharmacokinetic And Pharmacodynamimentioning
confidence: 99%
“…In recent years, there has been an increasing interest in the application of receptor theory in PK/PD modeling with the aim to predict in vivo concentration-effect relationships (Van der Graaf and Danhof, 1997). An important feature of these mechanism-based models is the strict distinction between drug-and system-related properties ( Van der Graaf et al, 1999;Visser et al, 2002;Zuideveld et al, 2004). A common feature of these models is that rapid equilibration of the drug-receptor complex is assumed.…”
mentioning
confidence: 99%
“…The incorporation of principles from receptor theory has been a key element in this development (Van der Graaf and Danhof, 1997). A specific feature of mechanism-based PK/PD models is the separation between a drug-specific part, characterizing the interaction of the drug with the biological system in terms of in vivo affinity and intrinsic efficacy, and a biological system-specific part characterizing the in vivo stimulus-response relationship (Visser et al, 2002;Zuideveld et al, 2004;Jonker et al, 2005). Typically the interaction of the drug with the biological system is described by a hyperbolic function.…”
mentioning
confidence: 99%